Analysis of nurses' job burnout and coping strategies in hemodialysis centers. Issue 17 (April 2020) - Ling, Kuang; Xianxiu, Wen; Xiaowei, Zhang
Abstract : Abstract: In recent years, nursing has come to be considered a high-risk and high-pressure profession, given the fast-paced working environment and constant need to handle emergencies, especially for nurses working in hemodialysis centers. Nearly every day, nurses are confronted with life and death situations and are required to provide skilled, high quality care for their patients, in fast-paced and demanding environments. Thus, nurses are susceptible to both psychological stress and other mental health problems, making them more vulnerable to burnout when compared against other healthcare professions. An anonymous online questionnaire was completed by a group of participating nurses, using the web-based survey platform WeChat. Registered nurses working in hemodialysis centers were randomly selected from 5 comprehensive tertiary level hospitals in Sichuan Province, China. The data collection instrument comprised two parts: demographic data and a nurse burnout questionnaire—the Maslach Burnout Inventory. Overall, 70 nurses were invited to participate, with 65 returning completed questionnaires, giving a response rate of 92.9%. In this survey, the burnout level was set at28.15 ± 12.39 for emotional exhaustion (EE), 10.23 ± 5.47 for depersonalization (DP), and 37.19 ± 8.31 for personal accomplishment (PA)—EE and DP levels are found to be high at the level of burnout. Job burnout was found to exist widely among the nurses of hemodialysis centers, which may then result in adverse effects on their physical and mental health. Active interventions can significantly reduce job burnout and also help maintain the stability of nursing workforce levels.